If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -33 + t = 38 Solving -33 + t = 38 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '33' to each side of the equation. -33 + 33 + t = 38 + 33 Combine like terms: -33 + 33 = 0 0 + t = 38 + 33 t = 38 + 33 Combine like terms: 38 + 33 = 71 t = 71 Simplifying t = 71
| c=9 | | (5x)(6x)= | | 5N+32=-52 | | X+4+21=x+x+2 | | 749x= | | 8y+100=6y+80 | | -25=-25 | | 6(9-1m)-12= | | 3b+17-1+8-16=100-4 | | -2(3x-2)=22 | | 3(c+d)+2c-c= | | 3b+17-1+8-4squared=100-4 | | 2(ab+abc+5)= | | -4(p+1)=-2(y+1)-5 | | 2(u+7)-9=19 | | 4-(5w-4)=-10w+8 | | 3N-20=22 | | 4x+8=96 | | 2q^2-11q=21 | | 7(5x-4)-1=8x | | 16x+5x+x= | | 4(2n+3)=7n-2 | | 4y^2+4x-4y=0 | | 2c-c= | | 30x-40= | | 3x-(2x-7)=7 | | 7x+(6x+1)=90 | | x-9y=16fory | | -3(a-1)=2(3a-12) | | 5w-40=2w+60 | | 2(4y+5)+4y=2(y+20) | | 17+3x=8x+2 |